Decoupling Thermoelectric Performance and Stability in Liquid‐Like Thermoelectric Materials. Issue 1 (19th October 2019) - Mao, Tao; Qiu, Pengfei; Hu, Ping; Du, Xiaolong; Zhao, Kunpeng; Wei, Tian‐Ran; Xiao, Jie; Shi, Xun; Chen, Lidong
Abstract: Liquid‐like materials are one family of promising thermoelectric materials discovered in the past years due to their advantanges of ultrahigh thermoelectric figure of merit ( zT ), low cost, and environmental friendliness. However, their practial applications are greatly limited by the low service stability from the Cu/Ag metal deposition under large current and/or temperature gradient. Both high zT for high efficiency and large critical voltage for good stability are required for liquid‐like materials, but they are usually strongly correlated and hard to be tuned individually. Herein, based on the thermodynamic analysis, it is shown that such a correlation can be decoupled through doping immobile ions into the liquid‐like sublattice. Taking Cu2− δ S as an example, doping immobile Fe ions in Cu1.90 S scarcely degrades the initial large critical voltage, but significantly enhances the zT to 1.5 at 1000 K by tuning the carrier concentration to the optimal range. Combining the low‐cost and environmentally friendly features, these Fe‐doped Cu2− δ S‐based compounds show great potential in civil applications. This study sheds light on the realization of both good stability and high performance for many other liquid‐like thermoelectric materials that have not been considered for real applications before. Abstract : Herein, the correlation between thermoelectric figure of merit and critical voltage is revealed and the thermodynamic analysis suggests that it can be decoupled through doping immobile ions into the liquid‐like sublattice. Along this direction, a new approach to design and fabricate liquid‐like materials with both high thermoelectric performance and good stability is proposed and well demonstrated in Cu2− δ S‐based liquid‐like materials.